2021
DOI: 10.1515/revneuro-2020-0131
|View full text |Cite
|
Sign up to set email alerts
|

The physiopathology of spontaneous hemorrhagic stroke: a systematic review

Abstract: Hemorrhagic stroke (HS) is a major cause of death and disability worldwide, despite being less common, it presents more aggressively and leads to more severe sequelae than ischemic stroke. There are two types of HS: Intracerebral Hemorrhage (ICH) and Subarachnoid Hemorrhage (SAH), differing not only in the site of bleeding, but also in the mechanisms responsible for acute and subacute symptoms. This is a systematic review of databases in search of works of the last five years relating to the comprehension of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…Firstly, we were unable to carry out further subgroup comparison of hemorrhagic stroke because the corresponding data were not available in the original articles. The mechanisms and risk factors for subarachnoid hemorrhage and intracerebral hemorrhage are different in important ways, as are treatment and outcomes ( 58 ). More clinical and mechanistic studies deserve further research.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we were unable to carry out further subgroup comparison of hemorrhagic stroke because the corresponding data were not available in the original articles. The mechanisms and risk factors for subarachnoid hemorrhage and intracerebral hemorrhage are different in important ways, as are treatment and outcomes ( 58 ). More clinical and mechanistic studies deserve further research.…”
Section: Discussionmentioning
confidence: 99%
“…They also found foci of contrast enhancement in 91% of expanded hematomas [16] . Although the precise pathophysiological mechanism underlying the formation of the spot sign remains unclear, some scholars propose that the spot sign's development may be linked to persistent bleeding around the hematoma, with consensus that the spot sign signi es contrast media leakage [17][18][19] . Prior studies have indicated that the spot sign exhibits greater reliability in predicting an unfavorable prognosis compared to other markers such as the black hole sign, blend sign, and island sign [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Though the strength of the association between LWH and stroke was moderate compared with other occupational exposures, the high prevalence of LWH lead to an estimated 400 000 deaths by stroke in 2016, with a population attributable fraction close to 7% 1. Stroke, however, is a broad term that conflates two different types of disease with different pathophysiology: ischaemic stroke is caused mainly by the clotting of a cerebral artery and haemorrhagic stroke is caused by the rupture of a cerebral artery 4 5. The WHO/ILO systematic review did not report enough information to differentiate the effect of LWH on risk of stroke subtypes.…”
Section: Introductionmentioning
confidence: 99%